2006
DOI: 10.2105/ajph.2004.060442
|View full text |Cite
|
Sign up to set email alerts
|

Social Support as a Buffer for Perceived Unfair Treatment Among Filipino Americans: Differences Between San Francisco and Honolulu

Abstract: Local contexts may influence the types of treatment encountered by members of ethnic minority groups, as well as their resources. These factors in turn may have implications for health disparities and well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
109
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(115 citation statements)
references
References 62 publications
4
109
1
1
Order By: Relevance
“…The range was 0 to 12 in this sample. Versions of the MOS have been used cross-culturally with immigrant and minority samples (Alonso et al, 2004;Lubetkin, Jia, & Gold, 2003;Peek, Ray, Patel, Stoebner-May, & Ottenbacher, 2004), including in prior studies of Filipino Americans specifically (de Castro et al, in press;Gee et al, 2006) and Asian Americans generally (Gee, Spencer, Chen, & Takeuchi, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…The range was 0 to 12 in this sample. Versions of the MOS have been used cross-culturally with immigrant and minority samples (Alonso et al, 2004;Lubetkin, Jia, & Gold, 2003;Peek, Ray, Patel, Stoebner-May, & Ottenbacher, 2004), including in prior studies of Filipino Americans specifically (de Castro et al, in press;Gee et al, 2006) and Asian Americans generally (Gee, Spencer, Chen, & Takeuchi, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…shown that unfair treatment is associated with chronic health conditions 45 and with depressive symptoms 46 among this population.…”
mentioning
confidence: 86%
“…A detailed description of this study can be found elsewhere. 45 To be included in the study, individuals had to be of Illicit drug use. Questions about lifetime use of illicit drugs were adapted from the UM-CIDI.…”
Section: Samplementioning
confidence: 99%
“…Sosyal destek, insanların ilişki bağlarından aldıkları kaynakları ifade eder [7]. Doğal destek sistemlerinin psikolojik sorunların çözümlerini kolaylaştırma veya zorlaştırmada önemli rol oynadıkları belirtilmektedir [8,9].…”
Section: Introductionunclassified